2020
DOI: 10.1002/syn.22146
|View full text |Cite
|
Sign up to set email alerts
|

Administration of moclobemide facilitates fear extinction and attenuates anxiety‐like behaviors by regulating synaptic‐associated proteins in a rat model of post‐traumatic stress disorder

Abstract: Post‐traumatic stress disorder (PTSD) is a long‐lasting mental disorder and accompanied by worse fear extinction. Enhanced fear memory or poor fear extinction are typical features of PTSD. Dysfunction of the serotonergic neurotransmitter system is involved in numerous mental and behavioral disorders. Monoamine oxidase A (MAOA) is important in the metabolism of serotonin and play an important role in behavious. The aim of this study was to explore the change of MAOA and effect of MAOA on fear memory in PTSD. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Increased ROS leads to the degeneration of striatal neurons, while DOPAC induces α-synuclein aggregation, a pathological hallmark of the PD brains. , Also, increased MAO-B activity is observed in AD brains . Recent studies showed that moclobemide, a clinically approved MAO-A inhibitor for depression, significantly reduced anxiety-like behavior and enhanced fear memory in stressed mice, facilitated smoking cessation and improved anti-Parkinson effect of levodopa treatment . Beside a neurological role, MAO-A inhibition could protect the myocardial damage due to the ROS generation in peripheral tissues resulting from the MAO-A oxidation and suppress cell growth, proliferation, and metastasis of cancer cells such as prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS leads to the degeneration of striatal neurons, while DOPAC induces α-synuclein aggregation, a pathological hallmark of the PD brains. , Also, increased MAO-B activity is observed in AD brains . Recent studies showed that moclobemide, a clinically approved MAO-A inhibitor for depression, significantly reduced anxiety-like behavior and enhanced fear memory in stressed mice, facilitated smoking cessation and improved anti-Parkinson effect of levodopa treatment . Beside a neurological role, MAO-A inhibition could protect the myocardial damage due to the ROS generation in peripheral tissues resulting from the MAO-A oxidation and suppress cell growth, proliferation, and metastasis of cancer cells such as prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…With these overall aims, we selected the SPS model, one of the most popular paradigms in the field of preclinical PTSD modeling, combined with fear extinction retention as a test for behavioral changes relevant to PTSD to conduct an in depth methodological review to determine sources of variability and develop optimization guidelines to enhance reproducibility across laboratories. SPS is widely applied to probe multiple PTSD-relevant phenotypes (behavioral and physiological) and putative trauma mechanisms [oxytocin regulation, the neuropeptide Y (NPY) system, synaptic protein expression, and memory function] (Serova et al, 2019;Hirota et al, 2020;Liu et al, 2020;Nwokafor et al, 2020;Xiao et al, 2020). This model has a number of elements that support its adoption including: (1) SPS has defined core features that support a capacity for reproducibility (i.e., restraint for 2 h, forced swim for 20 min, and ether until loss of consciousness to promote activation of the HPA axis; Yamamoto et al, 2009;Lisieski et al, 2018), (2) the use of SPS in mice and rats, (3) its initial development to probe PTSD-specific phenotypes including glucocorticoid receptor hypersensitivity and disrupted fear extinction, (4) its stress/incubation timeline that allows manipulation at various intervention points, and (5) SPS does not rely on post-hoc sorting of susceptible animals (e.g., social defeat).…”
Section: Introductionmentioning
confidence: 99%
“…Flores et al, 2014; Johnson, Molosh, et al, 2012; Soya et al, 2017; Strawn et al, 2010; Wilson et al, 2019; Yu et al, 2016). In our previous research, we demonstrated that significant behavioral changes in rats 7 days after SPS stimulation (Ding et al, 2017; F. Han et al, 2014; L. Wen et al, 2017; Xiao et al, 2020). Therefore, we chose this timepoint (7 days after SPS) as the time point for behavioral tests in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous research, we demonstrated that significant behavioral changes in rats 7 days after SPS stimulation (Ding et al, 2017;F. Han et al, 2014;Xiao et al, 2020). Therefore, we chose this timepoint (7 days after SPS) as the time point for behavioral tests in the present study.…”
Section: Immunocytochemical Labeling Of Retinal Wholemountsmentioning
confidence: 99%